Hypertextuality representation in a novel of J. Barnes: a history of the world in 10½ chapters - Anna Shlipatska (LADU: Journal of Languages and Education, 2021)
Background: The 21st century is marked by a drastic development of computer technology, which caused the growing interest in the hypertext. Despite the fact that it is mainly associated with the informational technology, the hypertext has also been a center of cross-disciplinary researches, as well as in the field of text linguistics. Purpose: Hence, the present article deals with the hypertextuality phenomenon in the emotive prose. Design and methods: By implementing the methods of comparative, structural, contextual, and intertextual analysis, the compositional and linguistic means of its representation are investigated on the basis of the novel by J. Barnes A History of the World in 10 ½ Chapters. Results: Julian Barnes is one of the most popular contemporary British writers. He is considered a postmodernism icon, whereas an American writer and critic J. C. Oates calls him a “pre-postmodernist”. He is an author to more than 20 novels. A History of the World in 10 ½ Chapters (1989) is a novel where the author experimented with a form. The book consists of ten novellas and Parenthesis. As far as the novel is considered an icon of postmodernistic literature, the revelation of a hypertext system there makes it possible to claim hypertextuality a distinctive marker of a postmodernistic perception of the world.